2020
DOI: 10.1038/s41598-020-59530-1
|View full text |Cite
|
Sign up to set email alerts
|

SLAM family member 8 is expressed in and enhances the growth of anaplastic large cell lymphoma

Abstract: Signaling lymphocytic activation molecule family member 8 (SLAMF8) / B-lymphocyte activator macrophage expressed/CD353 is a member of the CD2 family. SLAMF8 suppresses macrophage function but enhances the growth of neoplastic mast cells via SHP-2. In this study, we found that some anaplastic large cell lymphoma (ALCL) samples were immunohistochemically positive for SLAMF8. However, we found no significant differences between SLAMF8-positive and SLAMF8-negative ALCL samples with respect to age, gender, site, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…SLAMF8/CD353 is a member of the SLAMF receptor family that modulates the activation and functions of many immune cells. 50 , 51 Previous studies indicated that SLAMF8 was a diagnostic and prognostic marker for pulmonary tuberculosis, 31 glioma 23 and anaplastic large cell lymphoma. 51 Zeng et al 25 demonstrated that the combined deficiency of SLAMF8 and SLAMF9 could prevent endotoxin-induced hepatic inflammation, and could act as the promising therapeutic targets for acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLAMF8/CD353 is a member of the SLAMF receptor family that modulates the activation and functions of many immune cells. 50 , 51 Previous studies indicated that SLAMF8 was a diagnostic and prognostic marker for pulmonary tuberculosis, 31 glioma 23 and anaplastic large cell lymphoma. 51 Zeng et al 25 demonstrated that the combined deficiency of SLAMF8 and SLAMF9 could prevent endotoxin-induced hepatic inflammation, and could act as the promising therapeutic targets for acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“… 50 , 51 Previous studies indicated that SLAMF8 was a diagnostic and prognostic marker for pulmonary tuberculosis, 31 glioma 23 and anaplastic large cell lymphoma. 51 Zeng et al 25 demonstrated that the combined deficiency of SLAMF8 and SLAMF9 could prevent endotoxin-induced hepatic inflammation, and could act as the promising therapeutic targets for acute liver injury. However, our findings demonstrated a significant increase in the expression of SLAMF8 in HBV-related liver injuries, and its level increased with the severity of these injuries ( Figures 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…4). SLAMF8/CD353 is a member of the SLAMF receptor family that modulates the activation and functions of many immune cells [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…4). SLAMF8/CD353 is a member of the SLAMF receptor family that modulates the activation and functions of many immune cells [31,32]. Zeng et al [33] demonstrated that the combined de ciency of SLAMF8 and SLAMF9 could prevent endotoxin-induced hepatic in ammation and might serve as promising therapeutic targets for acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…This shared effect was also observed in the specific list of genes whose expression was altered in response to these ORFs (S2 Fig) . While more modest, we also observed that the HITS for IBD ORFs ETS2 and ZBTB40 shared a significant GO annotation (immune system process) (S3A, S3B, S4A and S5A Tables). Expressing the ORFs of ETS2 or ZBTB40 in THP-1 cells resulted in up-or down-regulation of a common set of genes (S3 Fig) primarily involved in the recruitment and extravasation of inflammatory cells [20][21][22][23][24]. While much more limited in terms of shared impact on the THP-1 transcriptome, the three shared HITs of SLC39A11 and NOD2 (S4 Fig) all impact on monocyte/macrophage polarization [25][26][27].…”
Section: Multiple Ibd Genes Have Shared Impacts On the Thp-1 Transcri...mentioning
confidence: 99%